Enabling Communications in Heterogeneous Multi-Agent Systems: Electricity Markets Ontology - Santos, Gabriel; Pinto, Tiago; Vale, Zita; Praça, Isabel; Morais, Hugo (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2016)
Electricity markets worldwide are complex and dynamic environments with very particular characteristics, resulting from their restructuring and evolution into regional and continental scales, along with the constant changes brought by the increasing necessity for an adequate integration of renewable energy sources. The rising complexity and unpredictability in electricity markets has increased the need for the intervenient entities in foreseeing market behaviour. Several modelling tools directed to the study of restructured wholesale electricity markets have emerged. However, they have a common limitation: the lack of interoperability between the various systems to allow the exchange of information and knowledge, to test different market models and to allow market players from different systems to interact in common market environments. This paper proposes the Electricity Markets Ontology, which integrates the essential necessary concepts related with electricity markets, while enabling an easier cooperation and adequate communication between related systems. Additionally, it can be extended and complemented according to the needs of other simulators and real systems in this area